A pilot cluster randomised trial of the Medicinesand Alcohol Consultation (MAC): an intervention to discuss alcohol use in community pharmacy medicine review services - Duncan Stewart; Anne van Dongen; Michelle Watson; Laura Mandefield; Karl Atkin; Ranjita Dhital; Brent Foster; Brendan Gough; Catherine Hewitt; Mary Madden; Stephanie Morris; Ronan O'Carroll; et al. (BMC, 2020)
Abstract Background Alcohol interventions are important to the developing public health role of community pharmacies. The Medicines and Alcohol Consultation (MAC) is a new intervention, co-produced with community pharmacists (CPs) and patients, which involves a CP practice development programme designed to integrate discussion of alcohol within existing NHS medicine review services. We conducted a pilot trial of the MAC and its delivery to investigate all study procedures to inform progression to a definitive trial. Methods This cluster pilot RCT was conducted in 10 community pharmacies in Yorkshire, UK, with a CP from each who regularly conducted Medicine Use Review (MUR) and New Medicine Service (NMS) consultations. Randomisation was conducted using a secure remote randomisation service. Intervention CPs (n = 5) were trained to deliver the MAC in MUR/NMS consultations. Control CPs (n = 5) provided these services as usual. Consecutive MUR/NMS patients were asked by CPs to participate, screened for eligibility (consumption of alcohol at least twice per week), and baseline data collected for those eligible. A two-month follow-up telephone interview was conducted. Blinding of CPs was not possible, but patients were blinded to the alcohol focus of the trial. Primary outcomes were total weekly UK units (8 g of ethanol per unit) of alcohol consumption in the week prior to follow-up, and confidence in medications management. Trial procedures were assessed by recruitment, attrition, and follow-up rates. Results 260 patients were approached by CPs to take part in the trial, 68% (n = 178) were assessed for eligibility and 30% (n = 54) of these patients were eligible. Almost all eligible patients (n = 51; 94%) consented to participate, of whom 92% (n = 47) were followed-up at 2 months; alcohol consumption was lower in the intervention arm and confidence in medication management reduced slightly for both groups. Exploration of recall issues at follow-up showed a high level of agreement between a two-item quantity/frequency measure and 7-day guided recall of alcohol consumption. Conclusions The pilot trial demonstrates the feasibility of implementing the MAC in community pharmacy and trial recruitment and data collection procedures. However, decommissioning of MURs means that it is not possible to conduct a definitive trial of the intervention in this service. Trial registration ISRCTN57447996